Regional Dimension of history of Organs of GPU-OGPU: to the analysis of monograph by A. B. Gularyan and A. Yu. Sarana - A. V. Sushko (Омский научный вестник: Серия "Общество. История. Современность")
The article characterizes the monograph of the Oryol researchers A. B. Gularyan and A. Yu. Saran, specialists in the history of domestic special services. The publication provides a comprehensive study of the structure, main directions and regional features of the activities of the GPU-OGPU bodies in the Omsk Irtysh region and the Oryol Pooch region in 1922–1934. The article analyzes the strengths and weaknesses of the monograph. It is emphasized that it contributes to the study of the political, social and everyday history of the early Soviet society. As a merit of the authors, an innovative approach to the study and comparison of the activities of the regional structures of the Soviet special services in different regions that are significantly distant from each other is noted. It is concluded that Russian historians should support and continue such an undertaking, expanding its scope geographically and chronologically. This, in general, will allow us to look at the history of state security agencies from a new angle and significantly complement scientific knowledge about their past.